Adaptation to Leftward Shifting Prisms Alters Motor Interhemispheric Inhibition - Martín-Arévalo, Elisa; Schintu, Selene; Farnè, Alessandro; Pisella, Laure; Reilly, Karen T (Cerebral cortex (New York, N.Y. 1991), 2018)
Abstract Adaptation to rightward shifting prisms (rightward prism adaptation, RPA) ameliorates neglect symptoms in patients while adaptation to leftward shifting prisms (leftward prism adaptation, LPA) induces neglect-like behaviors in healthy subjects. It has been hypothesized that prism adaptation (PA) modulates interhemispheric balance between the parietal cortices by inhibiting the posterior parietal cortex (PPC) contralateral to the prismatic deviation, but PA's effects on interhemispheric inhibition (IHI) have not been directly investigated. Since there are hyper-excitable connections between the PPC and primary motor cortex (M1) in the left hemisphere of neglect patients, we reasoned that LPA might mimic right hemisphere lesions by reducing parietal IHI, hyper-exciting the left PPC and PPC-M1 connections, and in turn altering IHI at the motor level. Namely, we hypothesized that LPA would increase IHI from the left to the right M1. We examined changes in left-to-right and right-to-left IHI between the 2 M1s using the ipsilateral silent period (iSP) (Meyer et al. 1995) before and after either LPA or RPA. The iSP was significantly longer after LPA but only from left-to-right and it did not change at all after RPA. This is the first physiological demonstration that LPA alters IHI in the healthy brain.